+0  
 
0
105
1
avatar

If f(x)=5x-12, find a value for $x$ so that $f^{-1}(x)=f(x-1)$.

 Feb 13, 2021
 #1
avatar+120124 
+1

f(x - 1)   = 5(x - 1)  -12  =   5x  - 17

 

Find  the  inverse

 

y = 5x  -12

 

y + 12 =  5x

 

(y + 12)  / 5    = x      "swap"  x and y

 

(x + 12)   / 5   = y    = the inverse

 

So

 

(x + 12)   / 5  =  5x  + 17

 

x + 12  =  5  ( 5x  + 17)

 

x + 12   = 25x   +  85

 

x - 25x  =    85   -12

 

-24x  = 73

 

x =  -73 / 24

 

 

cool cool cool

 Feb 13, 2021

22 Online Users

avatar
avatar
avatar
avatar